2020
DOI: 10.3390/biomedicines8040085
|View full text |Cite
|
Sign up to set email alerts
|

PBMC of Multiple Sclerosis Patients Show Deregulation of OPA1 Processing Associated with Increased ROS and PHB2 Protein Levels

Abstract: Multiple sclerosis (MS) is an autoimmune disease in which activated lymphocytes affect the central nervous system. Increase of reactive oxygen species (ROS), impairment of mitochondria-mediated apoptosis and mitochondrial alterations have been reported in peripheral lymphocytes of MS patients. Mitochondria-mediated apoptosis is regulated by several mechanisms and proteins. Among others, optic atrophy 1 (OPA1) protein plays a key role in the regulating mitochondrial dynamics, cristae architecture and release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Data reported that the plasma of MS patients show a lower antioxidant capacity [ 61 ] and higher levels of oxidative damage to lipid and proteins [ 61 , 62 ]. Our study conducted in PBMCs from 15 MS patients and 15 healthy subjects showed increased level of H 2 O 2 in MS with respect to healthy subjects [ 25 ] detected spectrofluorimetrically by dichlorodihydrofluorescin (DCFDA) probe. Interesting, the increased level of ROS production correlated with deregulation of some proteins involved in the mitochondrial dynamics and apoptosis [ 25 ].…”
Section: Oxidative Stress In Lymphocytes Of Msmentioning
confidence: 99%
See 4 more Smart Citations
“…Data reported that the plasma of MS patients show a lower antioxidant capacity [ 61 ] and higher levels of oxidative damage to lipid and proteins [ 61 , 62 ]. Our study conducted in PBMCs from 15 MS patients and 15 healthy subjects showed increased level of H 2 O 2 in MS with respect to healthy subjects [ 25 ] detected spectrofluorimetrically by dichlorodihydrofluorescin (DCFDA) probe. Interesting, the increased level of ROS production correlated with deregulation of some proteins involved in the mitochondrial dynamics and apoptosis [ 25 ].…”
Section: Oxidative Stress In Lymphocytes Of Msmentioning
confidence: 99%
“…Our study conducted in PBMCs from 15 MS patients and 15 healthy subjects showed increased level of H 2 O 2 in MS with respect to healthy subjects [ 25 ] detected spectrofluorimetrically by dichlorodihydrofluorescin (DCFDA) probe. Interesting, the increased level of ROS production correlated with deregulation of some proteins involved in the mitochondrial dynamics and apoptosis [ 25 ]. Another report, carried out in PBMC of 34 MS and 24 healthy subjects, showed a higher concentration of anion superoxide in MS evaluated by flow cytometry, associated with a decrease in the protein content of the mitochondrial OXPHOS (complexes I–V) [ 24 ].…”
Section: Oxidative Stress In Lymphocytes Of Msmentioning
confidence: 99%
See 3 more Smart Citations